Video-based education messaging to enhance optimal uptake of malaria preventive therapy in pregnant women: a mixed methods study involving pregnant women and midwives in Uganda - Rita Nakalega; Denis Mawanda; Ruth Nabisere-Arinaitwe; Nelson Mukiza; Cynthia Ndikuno Kuteesa; Robert Menge; Clemensia Nakabiito; Jane Nabakooza; Abel Kakuru; Lynn Atuyambe; Philippa Musoke; Mary Glenn Fowler; et al. (Malaria Journal)
Abstract Background Malaria prevention during pregnancy significantly minimizes maternal–fetal adverse events. However, optimal uptake of malaria preventive therapy in pregnancy (MPTp) remains a major challenge for both women living with HIV and those without. In Uganda, suboptimal uptake of MPTp is primarily due to inadequate knowledge among women. This study aimed to develop and assess the feasibility and acceptability of an educational video to improve knowledge of MPTp among pregnant women living with and without HIV. Methods This study describes the second phase of a mixed methods study conducted among pregnant women (living with and without HIV) and midwives from a public antenatal care clinic in Kampala, Uganda. The study was conducted from October 2022 to Jan 2024, and the first phase involved qualitative data collection from pregnant women, health workers, and Ministry of Health officials to develop a video-based intervention to enhance uptake of MPTp. The second phase involved administration of the developed intervention to a group of purposively selected pregnant women living with and without HIV. Questionnaires, focus group discussions, and interviews were used to collect data among women and midwives, and to assess feasibility and acceptability of the intervention. Quantitative data were summarized using descriptive statistics and analysed using different scales of measurement including the modified system usability scale and the Evidence-based Practice and Attitude Scale (EBPAS), which assessed acceptability among pregnant women and midwives, respectively. The qualitative data were coded and analysed using inductive and deductive thematic methods in Atlas ti.8. Results A total of 45 women and six midwives were enrolled in the current study phase. The mean age (± standard deviation, SD) of the women was 26 ± 6 years, and the median gestational age (interquartile range, IQR) was 24 (20–32) weeks, and less than half (42%, n = 19) were living with HIV. On the system usability scale, most women (91%, n = 41) rated the intervention as good or excellent, and most (93%, n = 42) were satisfied or very satisfied with the intervention. On the EBPAS, midwives perceived the intervention as reliable with Cronbach’s alpha of 0.74, and all midwives found the intervention appropriate and feasible in their facility. All women comprehended and highly accepted the intervention. Conclusion The video-based intervention for uptake of MPTp was found acceptable among women and midwives and was feasible and appropriate to a public health facility. Future studies would test the effectiveness of the intervention in improving knowledge and uptake of MPTp.